Highly Efficient CRISPR-Mediated Base Editing in Sinorhizobium meliloti - Wang, Longxiang; Xiao, Yuan; Wei, Xiaowei; Pan, Jimin; Duanmu, Deqiang (Frontiers in Microbiology, 2021)
Rhizobia are widespread gram-negative soil bacteria and indispensable symbiotic partners of legume plants that facilitate the most highly efficient biological nitrogen fixation in nature. Although genetics study in Sinorhizobium meliloti advanced the development of symbiotic nitrogen fixation (SNF) investigations, current genetic manipulation approaches are still time-consuming and labor-intensive. In this study, we report the development of a few precise gene modification tools by harnessing CRISPR/Cas9 system and various deaminases. By combining the fusion of Cas9 nickase and adenine deaminase, the adenine base editors (ABEs) system facilitated adenine-to-guanine transition at a one-nucleotide resolution without forming double-strand breaks (DSB). To replace the adenine deaminase with cytidine deaminase and other auxiliary enzyme components, we further engineered the cytidine base editors (CBEs) and guanine base editors (GBEs) that resulted in the cytidine-to-thymine substitution and cytidine-to-guanine transversion, respectively. All the base editors are amenable to the assembly of multiple synthetic guide RNAs (sgRNAs) cassettes by Golden Gate Assembly to achieve multigene mutations or disruptions simultaneously. Application of CRISPR-mediated base editing would accelerate the functional genomics and genome manipulation of rhizobia.